The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1186/s12939-018-0811-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an organised screening program on socioeconomic inequalities in mammography practice, knowledge and attitudes

Abstract: BackgroundBreast cancer stands as the leading cause of cancer related mortality in women worldwide. Mammography screening has the potential to improve prognosis by reducing stage at diagnosis. Socioeconomic inequalities in mammography cancer screening have been widely reported. The influence of organised programs on socioeconomic disparities regarding mammography screening is to date unclear. We aimed to investigate the impact of an organised regional screening program on socioeconomic inequalities in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Several studies have investigated the impact of organized screening programs on the reduction of socioeconomic disparities in the attendance of cancer screening activities, using different approaches. Indeed, the role of mammography screening programs in lessening socioeconomic inequalities in mammography practice was revealed in a study reporting the results of two cross-sectional studies in Switzerland before and after the implementation of an organized screening program [ 32 ], and a pooled, cross-sectional time series analysis evaluating secondary data from 17 European countries found that where organized screening programs are available, socioeconomic variables, such as education, income and type of employment or unemployment, are not related to attendance to screening and concluded that organized screening programs may reduce the socioeconomic inequalities in attendance to these preventive interventions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the impact of organized screening programs on the reduction of socioeconomic disparities in the attendance of cancer screening activities, using different approaches. Indeed, the role of mammography screening programs in lessening socioeconomic inequalities in mammography practice was revealed in a study reporting the results of two cross-sectional studies in Switzerland before and after the implementation of an organized screening program [ 32 ], and a pooled, cross-sectional time series analysis evaluating secondary data from 17 European countries found that where organized screening programs are available, socioeconomic variables, such as education, income and type of employment or unemployment, are not related to attendance to screening and concluded that organized screening programs may reduce the socioeconomic inequalities in attendance to these preventive interventions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…relationships between socio-economic variables and participation rate) should be informed not only by the pooled summaries but also by the national statistical data. Intervention studies show that removal of health system and financial barriers is positively associated with participation, and cancer disparities being reduced through organized screening, 43 46 although these efforts are not equally effective in all the jurisdictions.…”
Section: Discussionmentioning
confidence: 99%
“…Equity aspects are also very important for successful implementation of BC screening; however, inequalities in attendance still exist in many countries [25,29,30]. Our data are consistent with previous results showing that a higher level of education is associated with the higher rates of participation in BC screening [18,19,20,30]. Better educated women have a greater interest in health, more knowledge about health issues, and better access to resources for health improvement [31].…”
Section: Discussionmentioning
confidence: 99%
“…Better educated women have a greater interest in health, more knowledge about health issues, and better access to resources for health improvement [31]. A study carried out in Switzerland revealed that less-educated women had worse knowledge and more negative attitudes regarding mammography screening compared to women with a higher level of education [30]. On the other hand, education may have an impact on health through work and economic conditions.…”
Section: Discussionmentioning
confidence: 99%